RADIOLOGICAL DENTAL CHARACTERISTICS OF AGENESIS OF PERMANENT UPPER LATERAL INCISORS AND ITS FREQUENCY AMONG ORTHODONTIC PATIENTS - Kuroiedova, V.D.; Korobov, P.S.; Vyzhenko, Ye.Ye.; Halych, L.B. (World of Medicine and Biology, 2024)
Agenesis of the upper lateral incisors, in general, is a multifactorial clinical symptomless pathology with impaired aesthetics, function and psychological problems in patients. The aim of the study was to identify dental radiological features in orthodontic Ukrainian patients with agenesis of upper lateral incisors on orthopantomograms and to determine the frequency of occurrence of agenesis among orthodontic Ukrainian patients by an observational cross-sectional study. Orthopantomograms of 30 patients aged 7–25 years who had agenesis of permanent upper lateral incisors were found, analyzed and measured. According to the results of our study, in female patients, the presence of agenesis of the permanent upper lateral incisors has a significant direct relationship with the angles of inclination of central incisors (r=0.847, p=0.0), with the presence of temporary lateral incisors (r=0.972, p=0.0) and with the angles of inclination of canines (r=0.532, p=0.002). In male patients, a direct correlation of the presence of agenesis of the permanent upper lateral incisors was found with the angles of inclination of central incisors (r=0.815, p=0.000), with the presence of temporary lateral incisors (r=0.972, p=0.000) and with the angles of inclination of canines (r=0.532, p=0.002). The frequency of agenesis of upper lateral incisors among Ukrainian orthodontic patients is 1.9 %.